Use and development of building contracts and specifications in Amsterdam building organization up to 1654 (Bulletin KNOB, 2009)
The article consists of a first survey of historical building contracts and specifications as a historical source. In the Netherlands building contracts and specifications have not been subject of systematic study at all. The development of building specifications and building contracts can be brought into relation with the transition from wage labour to tender labour.From the end of the fifteenth century the contracts were becoming more detailed and, consequently, they supply more specific information about the object to be built. On the other hand, they contained more guarantees for the building commissioner. The first contracts and specifications were drawn up for municipal and religious building projects. In the seventeenth century the amount of contracts and specifications, drawn up for civilian projects, increased rapidly. The agreements that were made evolved from letters of appointment and delivery contracts according to sometimes very detailed specifications. Agreements were divided according to guild structures, which sometimes ended in conflicts. In the middle of the seventeenth century the use of building specifications was so common, that Dutch emigrants applied them for building projects in North America.